Inclusion policy as a means of general secondary education humanizing - Meliakov , Anton; Zub, Alla (Theory and Practice of Public Administration, 2019)
Inclusion in all its diversity has always attracted the attention of scientists. This problem is best developed in the publications of specialists in the field of pedagogy and medicine. Theoreticians and practitioners of law, psychology, sociology, etc. are also actively working on it. At the same time, the managerial aspect of this issue remains relatively less developed, and publications are not large in number. In the process of realization of education reforms, teachers’ opinions and attitudes should always be taken into account. Without educators who are well-motivated and positive towards inclusive education, it is impossible to ensure the rights of children with special educational needs. This is especially true in the context of decentralization, when significant powers in the development of public policy in the field of education are transferred from the central to the local level. To find out the secondary school teachers’ opinion, we conducted questionnaires in three schools of Kharkiv. The results of this study are the basis of this article. Most surveyed teachers are inclined to introduce inclusion positively and are well informed about its general principles. More than 40% of teachers consider inclusive education to be a logical step that will allow humanizing the education system in practice. 39.1% of respondents note that inclusive practices are a response to the demands of Ukraine’s foreign partners and the desire to achieve European educational standards. However, when the questions relate to concrete, practical steps, the opinions of respondents become more diverse, and the number of those who cannot determine their own position is significantly increasing. For example, activity of inclusive-resource centers is very differently evaluated. About 1/3 of respondents consider them to be necessary. But there is a big part of those teachers who are convinced that these centers are a burden for institutions of secondary education. Significantly, almost one in four of the respondents could not determine their opinion and chose the option "difficult to answer". It has been shown that teachers consider the availability of personnel and their worthy material support as an extremely important part of the reform. 60.8% of respondents identified the lack of qualified specialists as one of the main problems in the implementation of inclusion. However, in the first place (62.1%), there is a barrier of socio-psychological nature, namely: the unreadiness of "ordinary" children’s parents to their joint education with disabled students. At the same time, 50% of respondents are critical of the ability of the teachers themselves to engage in inclusive education. It is proved that, despite the complexity of implementation, inclusive education has good prospects. Most teachers predict its gradual development, which will lead to greater humanity and tolerance in the educational environment. Although we have 25% of skeptics who are convinced that inclusive education will not become habitual but will remain a social pedagogical experiment.